Does Social Media Promotion and Tourist Attraction Affect The Intention to Visit Tourist Destinations in Kuningan? Empirical Studies on Instagram - Agustin, Amelia; Syalfadhilah, Dinda; Maulany, Soesanty (International Journal of Social Service and Research, 2024)
In this era, social media has brought significant changes in the way businesses communicate and share information with consumers. This makes it easier for potential customers to obtain information as a decision-making flow. One natural tourism destination that recognizes the value of Instagram advertising is Woodland. Woodland has gained significant marketing attention as one of the natural tourist attractions. The reason for choosing this research object stems from the noteworthy progress of several marketing tactics, including digital-based promotion and brand revitalization, after the challenging 2019-2020 era in Woodland (caused by the COVID-19 epidemic), as a result of this noteworthy progress, there were 53.02% more visitors in 2022. This study used quantitative techniques. The t-table values obtained show that social media advertisements significantly influence the intention to visit woodland tourist attractions. The study's findings, which showed that Ha was approved while Ho was rejected, lend support to this claim. In addition, attractiveness significantly and positively affects the tendency of tourists to visit places that have forests. Visit intent is also influenced by social media attraction and advertising. Specifically, social media will create expectations for a destination so that it allows potential tourists to determine their vacation plans. Therefore, business people and related agencies must be able to pay more attention to the long-term management of social media and the attractiveness of their tourist destinations.